PERANCANGAN JEMBATAN I GIRDER DAN TRUSS SISTEM KOMPOSIT BENTANG 110 METER LAHAT SUMATERA SELATAN - Nurcahaya; Shapiyah, Sara; Marpaung, Raja; Lina Flaviana Tilik (Politeknik Negeri Sriwijaya, 2024)
A bridge is a construction that connects two or more separate areas. Bridges owned by PT. Bara Alam Utama is located in Banjarsari, Lahat Regency, South Sumatra. This bridge is used as an alternative way to bring mining products in the form of coal to the storage station. The total length of the bridge is 110 meters. This bridge is divided into 3 segments, namely the first segment is the beam I bridge, the second segment is the steel frame bridge and the third segment is the beam I bridge. The beam I bridge has a length of 25 m and the steel frame bridge has a length of 60 m. This bridge system uses a composite system of a combination of concrete and steel frames. The planning includes the superstructure and the substructure. From the results of the sondir test, the abutments and pillars are not able to withstand the sliding bearing capacity, therefore piles with a spunpile type with a diameter of 80 cm are used. Bridge planning is guided by RSNI T-12-2004, RSNI T-03-2005, SNI 2833-2016, SNI 1725-2016 and other library sources.